ANALISIS PENINGKATAN KINERJA KARYAWAN YANG DIPENGARUHI OLEH FAKTOR KOMPETENSI SDM, KARAKTERISTIK INDIVIDU DAN SEMANGAT KERJA KINERJA KARYAWAN BANK SARANA PRIMA MANDIRI PAMEKASAN - Slamet Riyanto; Nugroho Mardi Wibowo; Subijanto (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2021)
This type of research is explanatory research, the approach used is a quantitative approach with a total sample of 74 employees. The objectives of this study are 1). To test and analyze whether HR competencies, individual characteristics, and morale have a simultaneous and significant effect on employee performance at Bank Sarana Prima Mandiri Pamekasan. 2). To test and analyze whether HR competencies have a significant effect on employee performance at Bank Sarana Prima Mandiri Pamekasan. 3.) To test and analyze whether individual characteristics have a significant effect on the employee performance of Bank Sarana Prima Mandiri Pamekasan. 4.) To test and analyze whether morale has a significant effect on employee performance at Bank Sarana Prima Mandiri Pamekasan. The results showed that 1.) HR competence, individual characteristics and morale simultaneously have a significant influence on employee performance at Bank Sarana Prima Mandiri Pamekasan. 2.) HR competency has a significant influence on the employee performance of Bank Sarana Prima Mandiri Pamekasan, 3.) Individual characteristics have a significant effect on the employee performance of Bank Sarana Prima Mandiri Pamekasan. 4.) Morale has a significant effect on employee performance at Bank Sarana Prima Mandiri Pamekasan